Venetoclax combinations delay the time to deterioration of HRQoL in unfit patients with acute myeloid leukemia - Pratz, Keith W; Panayiotidis, Panayiotis; Recher, Christian; Wei, Xudong; Jonas, Brian A; Montesinos, Pau; Ivanov, Vladimir; Schuh, Andre C; DiNardo, Courtney D; Novak, Jan; Pejsa, Vlatko; Stevens, Don; et al. (Blood cancer journal, 2022)
Phase 3 trials Viale-A and Viale-C evaluated health-related quality of life (HRQoL) in patients with AML unfit for intensive chemotherapy who received venetoclax (VEN) + (AZA) (Viale-A) or low-dose cytarabine (LDAC) (Viale-C) or placebo (PBO) + AZA or LDAC. Patient-reported outcomes included: EORTC QLQ-C30 global health status (GHS/QoL) and physical functioning (PF), PROMIS Cancer Fatigue Short Form 7a (Fatigue), and EQ-5D-5L health status visual analog scale (HS-VAS). Time to deterioration (TTD), defined as worsening from baseline in meaningful change thresholds (MCT) of ≥10, 5, or 7 points for GHS/QoL or PF, fatigue, and HS-VAS, respectively, was assessed; differences between groups were analyzed using Kaplan-Meier and unadjusted log-rank analyses. VEN + AZA vs PBO + AZA patients had longer TTD in GHS/QoL (P = 0.066) and fatigue (P = 0.189), and significantly longer TTD in PF (P = 0.028) and HS-VAS (P < 0.001). VEN + LDAC vs PBO + LDAC patients had significantly longer TTD in GHS/QoL (P = 0.011), PF (P = 0.020), and fatigue (P = 0.004), and a trend in HS-VAS (P = 0.057). Approximately 43%, 35%, 32%, and 18% of patients treated with VEN + AZA, AZA + PBO, VEN + LDAC, or LDAC + PBO, respectively, saw improvements >MCT in GHS/QoL. Overall, VEN may positively impact HRQoL in patients with AML ineligible for intensive chemotherapy, leading to longer preservation of functioning and overall health status.
Keywords: bicyklické sloučeniny heterocyklické; Bridged Bicyclo Compounds, Heterocyclic; Sulfonamides; Cytarabine; únava; kvalita života; akutní myeloidní leukemie; Fatigue; lidé; Quality of Life; cytarabin; sulfonamidy; Antineoplastic Combined Chemotherapy Protocols; Humans; Leukemia, Myeloid, Acute; protokoly protinádorové kombinované chemoterapie